2019
DOI: 10.20961/carakatani.v35i1.30174
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield and Resistance Responses of Three Cultivars on True Seed Shallots to Twisted Disease with Salicylic Acid Application

Abstract: Twisted disease is one of the main diseases on shallot caused by <em>Fusarium </em>sp<em>.</em> One method to increase the resistance of shallot cultivars to the twisted disease can be performed by using True Seed Shallot (TSS) combining with a salicylic acid application. TSS is known as free pathogen. The objective of the research was to examine the effects of a salicylic acid application to the growth, yield and resistance responses of TSS on Tuktuk, Sanren and Lokananta cultivars to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(17 reference statements)
0
6
1
Order By: Relevance
“…The low productivity of TSS shallots was also influenced by the lack of production inputs used, both organic and inorganic fertilizers, and the spacing was not optimal. The increased growth and yield of TSS shallots can also be accomplished by the application of salicylic acid as was found [22].…”
Section: Growth and Yield Performance Of Tss Shallot Technologymentioning
confidence: 75%
“…The low productivity of TSS shallots was also influenced by the lack of production inputs used, both organic and inorganic fertilizers, and the spacing was not optimal. The increased growth and yield of TSS shallots can also be accomplished by the application of salicylic acid as was found [22].…”
Section: Growth and Yield Performance Of Tss Shallot Technologymentioning
confidence: 75%
“…The study results found that the incidence in control plants were still relatively low and might be related to the virulence of the pathogen used. Wijoyo et al (2020) showed that the incidence of moler disease on control plants from F. acutatum inoculation was only about 28.33% to 34.03%.…”
Section: Effect Of Application With Bacillus Spp In Disease Suppressionmentioning
confidence: 99%
“…F. acutatum isolates were grown on Potato Dextrose Agar (PDA) medium for seven days, then the spores were harvested and suspended to obtain a spore density of 10 6 CFU/ml. Pathogen inoculation was carried out by applying 10 mL of pathogen suspension to each plant during shallot planting (Wijoyo et al, 2020).…”
Section: Pathogen Inoculationmentioning
confidence: 99%
“…This condition is due to each variety having specific genetic characteristics in adapting to the growing environment, especially the availability of nutrients so that varieties will respond differently to growth [24] because each variety has different adaptability [5]. TSS varieties significantly affected plant growth [25].…”
Section: Growth Componentmentioning
confidence: 99%